Spectrum of genes for inherited hearing loss in the Israeli Jewish population, including the novel human deafness gene ATOH1. Issue 4 (24th August 2020) - Brownstein, Zippora; Gulsuner, Suleyman; Walsh, Tom; Martins, Fábio T.A.; Taiber, Shahar; Isakov, Ofer; Lee, Ming K.; Bordeynik‐Cohen, Mor; Birkan, Maria; Chang, Weise; Casadei, Silvia; Danial‐Farran, Nada; et al.
Abstract: Mutations in more than 150 genes are responsible for inherited hearing loss, with thousands of different, severe causal alleles that vary among populations. The Israeli Jewish population includes communities of diverse geographic origins, revealing a wide range of deafness‐associated variants and enabling clinical characterization of the associated phenotypes. Our goal was to identify the genetic causes of inherited hearing loss in this population, and to determine relationships among genotype, phenotype, and ethnicity. Genomic DNA samples from informative relatives of 88 multiplex families, all of self‐identified Jewish ancestry, with either non‐syndromic or syndromic hearing loss, were sequenced for known and candidate deafness genes using the HEar‐Seq gene panel. The genetic causes of hearing loss were identified for 60% of the families. One gene was encountered for the first time in human hearing loss: ATOH1 (Atonal), a basic helix‐loop‐helix transcription factor responsible for autosomal dominant progressive hearing loss in a five‐generation family. Our results show that genomic sequencing with a gene panel dedicated to hearing loss is effective for genetic diagnoses in a diverse population. Comprehensive sequencing enables well‐informed genetic counseling and clinical management by medical geneticists, otolaryngologists, audiologists, and speech therapists and can be integrated into newborn screening for deafness. Abstract : A mutation extending the length of ATOH1 (Atonal), a basic helix‐loop‐helix transcription factor, is associated with progressive non‐syndromic hearing loss in a five‐generation family, revealed by the HEar‐Seq gene panel. Western blot analysis of wild‐type and mutant ATOH1 proteins showed a significantly slower rate of degradation for mutant compared to the wild‐type protein.